PUSAT KESEHATAN MASYARAKAT BANJARBARU TANGGAP PANDEMI DI KECAMATAN BANJARBARU SELATAN, BANJARBARU - Adawiyah, Raudhatul; Andini, Dila Nadya; Fawzia, Irma (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Public Health Facility is a first-level health facility, the development of which is the fulfillment of public health insurance in Indonesia. Public Health Facility that was originally managed by the central government underwent decentralization so that each region could manage Public Health Facility in their respective areas; this had an impact on the uneven quality and quantity of the workforce and infrastructure of Public Health Facility in Indonesia. The lack of quality of health centers will complicate health provision in certain areas. Global health problems, namely the Covid-19 pandemic, exacerbate the performance of Public Health Facilities which tend not to be ready to cope with changing conditions; resulting in a decrease in visitors and even some Public Health Facilities reducing their operational time. The efforts of countries in the world and the World Health Organization are to publish protocols for the prevention, detection and handling of Covid-19; and the use of technology is one of the solutions that facilitate activities during a pandemic. Appropriate technology methods with criteria according to Teartisup can be applied to the design of Public Health Facility so that health provision is guaranteed to be easy and safe, especially during a pandemic.